A Probiotic Lactobacillus gasseri Alleviates Escherichia coli-Induced Cognitive Impairment and Depression in Mice by Regulating IL-1β Expression and Gut Microbiota - Yun, Soo-Won (Nutrients, 2020)
Excessive expression of interleukin (IL)-1β in the brain causes depression and cognitive dysfunction. Herein, we investigated the effect of Lactobacillus gasseri NK109, which suppressed IL-1β expression in activated macrophages, on Escherichia coli K1-induced cognitive impairment and depression in mice. Germ-free and specific pathogen-free mice with neuropsychiatric disorders were prepared by oral gavage of K1. NK109 alleviated K1-induced cognition-impaired and depressive behaviors, decreased the expression of IL-1β and populations of NF-κB(+)/Iba1(+) and IL-1R(+) cells, and increased the K1-suppressed population of BDNF(+)/NeuN(+) cells in the hippocampus. However, its effects were partially attenuated by celiac vagotomy. NK109 treatment mitigated K1-induced colitis and gut dysbiosis. Tyndallized NK109, even if lysed, alleviated cognitive impairment and depression. In conclusion, NK109 alleviated neuropsychiatric disorders and colitis by modulating IL-1β expression, gut microbiota, and vagus nerve-mediated gut–brain signaling.